1979
DOI: 10.1128/iai.26.3.1079-1087.1979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbohydrate source and growth conditions on the production of lipoteichoic acid by Streptococcus mutans Ingbritt

Abstract: Streptococcus mutans Ingbritt was grown in a chemostat at defined dilution rates and pH values and under carbohydrate limitation. At a constant dilution rate of D = 0.1 h-' and with either 0.5% glucose or 0.5% sucrose, the amounts of both cellular and extracellular lipoteichoic acid increased as the culture pH increased from 5.0 to 7.5. At a constant pH of 6.0, the amount of cellular lipoteichoic acid formed by cultures growing in 0.2% or 0.5% glucose was relatively

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Standard medium consisted of the lowmolecular-weight fraction of Trypticase (BBL Microbiology Systems, Cockeysville, Md. )-yeast extract medium that passed through Amicon hollow fiber filter HlPlO (21). Glucose or fructose was added to a final concentration of 2% for batch culture experiments or 0.5% for continuous-culture experiments, and the medium was then sterilized by membrane filtration (21).…”
Section: Methodsmentioning
confidence: 99%
“…Standard medium consisted of the lowmolecular-weight fraction of Trypticase (BBL Microbiology Systems, Cockeysville, Md. )-yeast extract medium that passed through Amicon hollow fiber filter HlPlO (21). Glucose or fructose was added to a final concentration of 2% for batch culture experiments or 0.5% for continuous-culture experiments, and the medium was then sterilized by membrane filtration (21).…”
Section: Methodsmentioning
confidence: 99%
“…In strain NCTC 10302 the R-polysaccharide is not attached covalently to the cell wall, but is present as a capsule and in the culture fluid and is therefore better considered as a cell surfaceassociated component. In view of the previous observations on the effect of generation time on the production of other surface-associated components, namely, proteins and lipoteichoic acid (7)(8)(9)23), the variations in the amounts of capsular polysaccharide may not be surprising, although it should be noted that other studies found that growth rates did not influence exo- polysaccharide synthesis (10). Changing the carbohydrate source from glucose to fructose has also been shown to affect the production of lipoteichoic acid and certain proteins (7), but more relevant to the current study is the report that the production of extracellular polysaccharide by a strain of Actinomyces viscosus was much greater in glucose than in fructose (18).…”
Section: Discussionmentioning
confidence: 98%
“…A chemostat is particularly suitable for such a study as the influence of a parameter such as generation time, pH, or change of nutrient can be studied while other variables are controlled. By such means it has been shown, for example, that the production of the cell wall typing antigen of Streptococcus mutans Ingbritt is not affected by different growth conditions (17), whereas the amount of lipoteichoic acid can vary over a wide range (8). The production of lipoteichoic acid was enhanced markedly by a change of growth-limiting nutrient from glucose to fructose, an effect that could also be achieved in batch culture (17).…”
mentioning
confidence: 99%
“…The anti-L-cAg:Ab serum was examined for reactivity with the c polysaccharide and other glucose-containing polymers by using a passive hemagglutination assay as previously described (15). The additional polysaccharides included (i) RGP, prepared from S. mutans B13 (RGP/B13) (15), (ii) lipoteichoic acid, prepared from strain Ingbritt (LTA/Ingbritt) (7), and (iii) dextran T-10 purchased from Pharmacia Fine Chemicals. The purified c polysaccharide, RGP/B13, and dextran T-10 were esterified with palmitic acid according to the methods of Hammerling and Westphal (5) to facilitate sensitization of sheep erythrocytes for use in the passive hemagglutination assays.…”
mentioning
confidence: 99%
“…Although S. inltans is known to accumulate surface glucans and clump when grown in sucrose-supplemented batch culture, no cell clumping was noted, even microscopically, under chemostat conditions when sucrose was the limiting growth nutrient. Examination of antisera for reactivity with dextran by the passive hemagglutination assay pro- vided a sensitive means for detecting antibodies to surface-associated glucans in amounts that were not evident in earlier studies (7,8).…”
mentioning
confidence: 99%